Valuing Public Parks for Post-disaster Urban Recovery: Evidence from Rikuzentakata, Japan - Okuyama, Tadahiro (Journal of Economics Research and Social Sciences, 2026)
This study examines how an ordinary riverside park in a disaster-affected and shrinking city can be repositioned as social infrastructure supporting community recovery and urban resilience. Focusing on Kawahara River Park in Rikuzentakata, Japan, which was heavily damaged by the 2011 Great East Japan Earthquake, we conducted a contingent valuation survey with a stated-preference design to estimate residents’ and visitors’ willingness to pay (WTP) for park-based improvements such as events, cherry-tree planting, and preparedness facilities. Using multiple-bounded logit estimation, the study linked WTP outcomes to implementable policy choices for pricing and investment sequencing. The median WTP stabilized at JPY 1,600–1,700, interpreted as an upper bound for feasible fee levels. WTP increased significantly with event programming and symbolic landscape attributes (e.g., cherry-avenue scenery and community interaction), while hard preparedness facilities produced no additional WTP—consistent with the notion that safety infrastructure should be publicly financed. Based on these findings, the study proposes a phased policy portfolio: short-term event programming to strengthen local interaction and economic activity, followed by long-term investment in symbolic landscapes that sustain collective resilience. This research contributes to the literature by integrating disaster recovery, community resilience, and environmental valuation into a unified framework, demonstrating that even ordinary public parks can function as cost-effective social infrastructure for disaster risk reduction and sustainable urban recovery in resource-constrained regions.